2021
DOI: 10.37349/emed.2021.00059
|View full text |Cite
|
Sign up to set email alerts
|

A review of aortic thrombosis in COVID-19 infection

Abstract: Aim: As the novel coronavirus disease 2019 (COVID-19) pandemic impacts the global healthcare system, evolving data show increased frequency of arterial and venous thromboembolism among patients with COVID-19 infection. Aortic thrombus is a rare thrombotic event with a wide spectrum of clinical manifestations and potential catastrophic complications. This study aimed to elucidate the clinical manifestations, diagnosis and treatment dilemmas of aortic thrombus with COVID-19 infection and raise awareness among fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Although we now have some data for the incidence of DVT and pulmonary embolism in patients with COVID-19 infection, the data for aortic thrombus is scarce. Due to the scarcity of the data, it is hard to predict the exact incidence of aortic thrombosis in patients infected with COVID-19 [ 7 ]. The current data on aortic thrombosis in patients with COVID-19 infection is limited to the case report and case series.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although we now have some data for the incidence of DVT and pulmonary embolism in patients with COVID-19 infection, the data for aortic thrombus is scarce. Due to the scarcity of the data, it is hard to predict the exact incidence of aortic thrombosis in patients infected with COVID-19 [ 7 ]. The current data on aortic thrombosis in patients with COVID-19 infection is limited to the case report and case series.…”
Section: Discussionmentioning
confidence: 99%
“…The current data on aortic thrombosis in patients with COVID-19 infection is limited to the case report and case series. In one literature review, 43 cases of COVID-19-related aortic thrombosis were identified, and most of the patients were male and above age 50 [ 7 ]. The common comorbidities were smoking, obesity, hypertension, and diabetes mellitus [ 7 - 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations